On the mechanism activation of hydrogen and hydrocarbons on the carbides and hydrades obtained by non-isotermal conditions - P. S. Gukasyan (ՀՀ ԳԱԱ հրատ.)
Activation of ZrNiH3 hydride and TiCx carbides obtained by Self-propagating-High Temperature Synthesis (SHS) method, as well as of natural clinoptilolite was investigated by hydrogen and hydrocarbon in non-isotherm conditions. Positive influence of small quantities of oxygen was observed on activation process. It has been shown that after preliminary activation of carbides and the zeolite surface modified by Cr2O3 can be used as substrate in CO hydration process carried out by spillover method in soft conditions. Изучен процесс активации гидрида ZrNiH3, карбидов TiCx водородом и углеводородом, а также клиноптилолита в неизотермических условиях. Наблюдалось промотирующее действие следов кислорода на процесс активации. ZrNiH3 и TiCx синтезированы методом высокотемпературного самораспространяющегося синтеза. Показано, что активированный гидрид или карбид, комбинированный с модифицированным клиноптилолитом, можно успешно использовать для гидрирования CO в мягких условиях. Հետազոտվել է բարձրջերմաստիճանային ինքնատարածման սինտեզի (ԲԻՍ) մեթոդով ստացված ZrNiH3 հիդրիդի և TiCx կարբիդների, ինչպես նաև բնական կլինոպտիլոլիտի ջրածնով և ածխաջրածնով ակտիվացումը ոչ իզոթերմ պայմաններում: Նկատվել է թթվածնի հետքերի դրական ազդեցությունը ակտիվացման գործընթացի վրա: Ցույց է տրվել որ ակտիվացումից հետո հիդրիդը և կարբիդները զուգակցելով ակտիվացված և մոդիֆիկացված ցեոլիթի հետ, էֆեկտիվ կերպով իրականացնում են СО-ի հիդրում մեղմ պայմաններում:
Keywords: Քիմիա